Paraschistura kermanensis, a new stone loach species from southeastern Iran (Teleostei: Nemacheilidae) - Sayyadzadeh, Golnaz; Teimori, Azad; Esmaeili, Hamid Reza (Zootaxa, 2019)
Paraschistura kermanensis from the endorheic Kerman-Naein basin in Iran is distinguished from its closest congeners (P. abdolii, P. delvarii, P. kessleri and P. naumanni) by lacking scales on the flanks anterior to the dorsal-fin origin, having scales on the caudal peduncle, and having the pelvic-fin origin situated anterior to or below the vertical through the dorsal-fin origin. It is also characterised by six fixed diagnostic nucleotide substitutions and a K2P nearest neighbour distance of 4% to P. abdolii in the mtDNA COI barcode region.